Formation of a heterotic pattern with temperate and tropical maize lines - Balderrama Castro, Sigifredo; Ron Parra José; Sánchez González José de Jesús; Rodríguez Guzmán Eduardo; Adolfo Uhart, Sergio (Revista Mexicana de Ciencias Agrícolas, 2018)
In breeding programs corn (Zea mays L.) focused on the generation of hybrids, it is crucial to have sources of germplasm and have information about groups and heterotic patterns to help in planning the crossovers. This work was carried out with the purpose of forming a heterotic pattern based on the development of maize populations generated with two yellow temperate lines (Stiff Stalk (SS) and Non-Stiff Stalk (NSS) in crosses with two tropical white lines (Tuxpeño (TUX) and Hick (CAT)). With four possible single crosses lines (SS/TUX, SS/CAT, NSS/TUX and NSS/CAT) were formed, and these two double hybrids unrelated (SS/TUX//NSS/CAT and SS/CAT//NSS/TUX) to identify performance tests the best performance; which would indicate the best tropical- temperate combinations. The trials were established in five locations in the subtropics (Zapopan, Leon, Silao, Irapuato and Villagran, in the spring-summer 2011). The experimental design was a randomized complete block. The results showed different productive potential of double hybrids, with SS/TUX//NSS/CAT best, also highlighted by the grain moisture at harvest, root lodging and stalk, ear rot, Fusarium stalk rot and leaf spot Cercospora. Based on the results, a heterotic pattern formed by an "A" group that integrates with the combination of the lines Stiff Stalk and Tuxpeño and the opposite heterotic "B" formed by the cross of Non-Stiff Stalk lines group was defined and hick.